Adapting Great Plains Cropping Systems to a Changing Climate - Roozeboom, Kraig L. (Kansas State University, 2012)
Potential cropping system strategies for adapting to climate change include crop selection, tillage systems, plant breeding and technology. Water conservation can have significant impacts on corn yield. Conserving two inches of water can add 26 bushels/acre to corn yield.
Keywords: Agriculture; Climate change; Evapotranspiration; Yield; Corn; Sorghum